2015
DOI: 10.1177/0145445515583246
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Work-Reinforcer Schedules on Skill Acquisition for Children With Autism

Abstract: This study evaluated the effects of continuous and discontinuous work-reinforcer schedule arrangements on skill acquisition for three students with autism. Participants were initially exposed to both schedules in an alternating schedules condition where they were taught different but equivalent skills for each schedule. In the discontinuous schedule condition, participants completed work in small increments to gain access to a reinforcer for short periods of time. In the continuous schedule condition, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
2
13
0
1
Order By: Relevance
“…Although the accumulated exchange‐production schedules were associated with delays to reinforcement, they supported higher rates of work completion and were more preferred. These findings are consistent with other research suggesting accumulated exchange‐production schedules are more efficient and facilitate greater rates of work completion (Bukala, Hu, Lee, Ward‐Horner, & Fienup, ; Ward‐Horner, Cengher, Ross, & Fienup, ), and are more preferred relative to distributed exchange‐production schedules (e.g., Fienup, Ahlers, & Pace, ; Kocher, Howard, & Fienup, ).…”
Section: Introductionsupporting
confidence: 90%
“…Although the accumulated exchange‐production schedules were associated with delays to reinforcement, they supported higher rates of work completion and were more preferred. These findings are consistent with other research suggesting accumulated exchange‐production schedules are more efficient and facilitate greater rates of work completion (Bukala, Hu, Lee, Ward‐Horner, & Fienup, ; Ward‐Horner, Cengher, Ross, & Fienup, ), and are more preferred relative to distributed exchange‐production schedules (e.g., Fienup, Ahlers, & Pace, ; Kocher, Howard, & Fienup, ).…”
Section: Introductionsupporting
confidence: 90%
“…That is, the discontinuous arrangement in the present study consisted of two units of five responses with each unit followed by 5 min of reinforcer access, whereas the discontinuous arrangement in previous studies consisted of at least five response-reinforcer units with 30 s to 3 min of reinforcer access per unit. Furthermore, for three out of the five previous studies (Bukala et al, 2015;DeLeon et al, 2014;Kocher et al, 2015), the duration of continuous reinforcer access in the continuous arrangement was 5 min, which was the same duration of the discontinuous arrangement in the present study. Therefore, it is possible that the participants' initial preference was, in part, a function of fewer response-reinforcer units with longer duration reinforcer access in the discontinuous arrangement.…”
Section: Resultssupporting
confidence: 53%
“…There have been several replications of Fienup et al (2011) that have largely focused on variables influencing preference and performance for response-reinforcer arrangements with older participants who generally preferred a continuous arrangement (e.g., DeLeon et al, 2014;Kocher, Howard, & Fienup, 2015;Ward-Horner et al, 2014). For instance, DeLeon et al (2014) investigated the effects of the type of reinforcer on preference by providing access to edible and activity reinforcers.…”
mentioning
confidence: 99%
“…For example, clearer understanding of these variables may lead to the selection of different response‐reinforcer arrangements for different types of tasks and reinforcers (e.g., acquisition vs. maintenance tasks; activity‐based vs. edible reinforcers). There is a growing body of applied research examining variables that may affect preference for and performance under various response‐reinforcer arrangements (Bukala, Yao Hu, Lee, Ward‐Horner, & Fienup, 2015; DeLeon et al, ; Kocher, Howard, & Fienup, ; Ward‐Horner, Pittenger, Pace, & Fienup, ). This paper provides a review of these studies and discusses variables (see Table ) that likely influence preference and performance.…”
Section: Procedural and Qualitative Variables That May Influence Prefmentioning
confidence: 99%
“…Because maintenance tasks do not require learning, the less frequent reinforcer delivery inherent to continuous arrangements may have been a critical variable influencing preference and performance. Therefore, Kocher et al () extended the aforementioned studies by evaluating preference for and performance under continuous and discontinuous arrangements with skill acquisition tasks. The researchers found that (a) preference was mixed with one participant preferring each arrangement, respectively, and one participant demonstrating no differentiated preference, (b) the number of sessions to mastery did not differ for two of three participants, and (c) overall session duration was consistently shorter for the continuous arrangement for all three participants.…”
Section: Prior Researchmentioning
confidence: 99%